The impact of means tested assistance in Southern Europe - Cathal O'Donoghue; J. Albuquerque; Massimo Baldini; Olivier Bargain; P. Bosi; Horacio Levy; D. Mantovani; Manos Matsaganis; M. Mercader-Prats; C. Farinha; Farinha Rodrigues; S. Toso; et al. (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This paper aims to analyse the social assistance systems in five South European countries: France, Greece, Italy, Portugal and Spain. After reviewing the existing system of social assistance in each country, we apply a consistent methodology in order to estimate its impact on income distribution, poverty and target efficiency.
Keywords: D31; I38; 330; Social Assistance; Southern Europe; Microsimulation